P1522 Long term follow-up after early mitral valve surgery. Role of 3D echocardiographic right chambers evaluation in predicting tricuspid regurgitation development. (17th January 2020) - Volpato, V; Mantegazza, V; Manfredonia, L; Fusini, L; Gripari, P; Tamborini, G; Pepi, M
Abstract: Background: Combined mitral and tricuspid surgery is recommended in patients diagnosed with significant tricuspid regurgitation (TR) or dilatation of tricuspid annulus (TA) undergoing mitral valve (MV) surgery. Despite the prognostic value of significant TR is well known, the role of TA is still debated, due to inaccuracy of 2D measurements. Data about the role of 3D echocardiographic evaluation of TA and right chambers in predicting TR development after early MV surgery are lacking. Purpose: To test whether a comprehensive 3D evaluation of right chambers and TA may predict TR development after early surgery in patients with MV prolapse, at a long term follow-up. Methods: Between 2012 and 2015, 100 patients diagnosed with MV prolapse and severe mitral regurgitation, who underwent early MV repair were retrospectively studied. All patients underwent 3D transthoracic examination before surgery; for each patient right atrial (RA) volume and right ventricular (RV) volumes, function and strain were derived. 3D dimensions and function of TA were also measured using commercial software. The median follow-up was 48 months. Results: 9 patients underwent TVR for moderate TR and were excluded. At baseline, our patients showed more than moderate TR, normal 3D RV volumes and function (EDV 67 ±16ml/m2, EF 56 ± 6%, GLS free wall 28 ± 5 %) and RA volume (54 ± 15 ml/m2). Pulmonary artery pressure was 36 ±9 mmHg. Based on 2D evaluation, dilatation of TA (more than 21 mm/m2) was measured in 21 patients over 91. 3D analysis of TA showed a function of 38 ± 12% and a major axis of 46 ± 6 mm no significant differences in 3D values were noted between patients with normal and dilated annuli. Based on 2D. Over the follow-up, none of our patients developed clinically significant TR (more than moderate) Conclusion: Patients who underwent early MV repair with normal 3D values of right chambers have a low risk of developing TR, regardless of 2D dimensions of TA.